Dissecting the causal association of diet with thyroid cancer: a systematic review with meta-analysis and mendelian randomization analysis. - Kang, Chao; Du, Yongyao; Li, Jiaxin; Yang, Yi; Li, Jingping; Zhou, Manping; Shi, Jiaojiao; Lin, Ning; Ma, Xin; Peng, Xiaoli (Frontiers in Nutrition, 2025)
BackgroundDiet is a recognized risk factor for cancer. Recently, the role of improving thyroid-related functions through diet has been questioned. This systematic review investigates the relationship between food groups/dietary patterns and thyroid cancer.MethodsWe conducted a systematic search of the literature through April 2025 in the PubMed, Scopus, Web of Science, and Embase database following PRISMA guidelines. ORs, HRs or RRs with 95% CIs were extracted as effect sizes and publication bias was assessed using funnel plots. Additionally, we conducted mendelian randomization (MR) analysis by selecting dietary factors (including nutrients) associated with thyroid cancer as exposure data to complement the results of meta-analysis.ResultsWe collected data from 16 cohort and 21 case-control studies that met the collection criteria. Meta-analysis found that high consumption of fish and alcohol-containing beverages was associated with a reduced risk of thyroid cancer, whereas consumption of high amounts of refined cereal and nitrates increased thyroid cancer risk (P < 0.05). Our MR analysis data showed that some specific food items, especially seafood (like oily fish) might be the protective factors for thyroid cancer, which strengthen the previous meta-analysis results.ConclusionThis comprehensive study investigated the relationships between dietary factors and thyroid cancer risk, synthesizing findings from a meta-analysis of observational studies and MR analysis to estimate causal associations. Consistently, both the meta-analysis and MR analysis revealed that consumption of certain types of fish may be linked to a decreased risk of thyroid cancer.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251101506.